Transformasi Kadaster di Indonesia: Kepastian Hukum dalam Sejarah dan Tantangan Pendaftaran Tanah - Widarbo, Koes; Kusmiarto, Kusmiarto (Sekolah Tinggi Pertanahan Nasional, 2023)
ABSTRACT The history of the cadastre in Indonesia encompasses the periods of Dutch East Indies colonial rule, Japanese occupation, and the post-independence era. The enactment of Law No. 5 of 1960 concerning the Basic Agrarian Law (UUPA), particularly Article 19, which defines the scope of cadastre, has brought about significant changes. Nonetheless, the core issue remains the ineffectiveness of cadastre mapping in providing legal certainty, even serving as a recurring source of land-related problems, including during the periods of Presidential Regulations (PP) 10/1961, PP 24/1997, and PTSL. This research aims to comprehend the concept and historical mission of cadastre in each village or sub-district periodically and to assess its impact on land-related cases. The research employs normative legal methods and qualitative approaches. Conceptual, historical, comparative, and case study approaches are employed to gain a deeper understanding. Moreover, philosophical approaches (fundamental, comprehensive, and speculative) and ontological, epistemological, and axiological aspects are also considered for further research. The findings unveil the complexity and dynamics involved in land registration and cadastre management in Indonesia. Changes in regulations, ontological, and epistemological approaches, along with efforts to establish comprehensive registration maps, constitute vital components in maintaining effective legal certainty and land management. Keywords: cadastral history, Legal certainty, Land-related issues, Cadastral mapping, Land registration reform. INTISARI Sejarah kadaster di Indonesia meliputi era Pemerintahan Hindia Belanda, penjajahan Jepang, hingga era kemerdekaan. Berlakunya Undang-Undang nomor 5 tahun 1960 tentang UUPA, terutama Pasal 19 yang mengatur ruang lingkup kadaster, mengubah dinamika. Meski demikian, permasalahan inti adalah perpetaan kadaster yang kurang efektif dalam memberikan kepastian hukum, bahkan menjadi sumber berulangnya masalah pertanahan, termasuk di era PP 10/1961, PP 24/1997, dan PTSL. Penelitian ini bertujuan memahami konsep dan sejarah misi kadaster di setiap desa atau kelurahan secara periodik, serta membandingkan dampaknya pada kasus pertanahan. Metode hukum normatif dan pendekatan kualitatif digunakan. Pendekatan konseptual, sejarah, perbandingan, dan studi kasus diterapkan. Pendekatan filsafat (mendasar, menyeluruh, spekulatif) dan aspek ontologis, epistemologis, serta aksiologis juga dipertimbangkan untuk penelitian selanjutnya. Hasilnya mengungkapkan kompleksitas dan dinamika dalam penyelenggaraan pendaftaran tanah dan kadaster di Indonesia. Perubahan aturan, pendekatan ontologis dan epistemologis, serta upaya mewujudkan peta pendaftaran lengkap menjadi komponen penting dalam menjaga kepastian hukum dan pengelolaan pertanahan yang efektif. Kata Kunci: Sejarah kadaster, Kepastian hukum, Masalah terkait tanah, Pemetaan kadaster, Reformasi pendaftaran tanah